26th Annual Meeting of the German Society for Travel Medicine (DFR) Leipzig, Germany, 7–9 September 2023 - Küpper, Thomas (Health Promotion & Physical Activity, 2023)
This year the meeting included again a wide variety of topics. Beside of ‘typical’ ones like malaria (Rothe) or actual aspects concerning vaccinations (Burchard, Kling) other lecturers reported about international aid in the case of catastrophies (Schad), polar regions (Kohlberg), volcano tourism (Heggie), diving medicine (Koonen and Schröder), rare diseases like naegleria (Heggie), and even work in space (Ewald). A session focused tricky cases from daily routine travel medicine. There was also a special invitation to young scientists, students and clinicians with a specific event. Poster presentations added topics for discussions. The presented abstracts include lectures and posters and are listed in alphabetical order of the first author. The presented abstracts include lectures and posters and are listed in alphabetical order of the first author.